2022
DOI: 10.3988/jcn.2022.18.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Transcranial Direct Current Stimulation in Alzheimer’s Disease: Optimizing Trials Toward Clinical Use

Abstract: Transcranial direct current stimulation (tDCS) is a safe and well-tolerated noninvasive method for stimulating the brain that is rapidly developing into a treatment method for various neurological and psychiatric conditions. In particular, there is growing evidence of a therapeutic role for tDCS in ameliorating or delaying the cognitive decline in Alzheimer’s disease (AD). We provide a brief overview of the current development and application status of tDCS as a nonpharmacological therapeutic method for AD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 105 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…However, repeated sessions can produce cumulative and long-lasting modulations of neural activity and neuroplasticity [9,10]. tDCS has therefore gained attention as a potential therapeutic tool for use in a range of various neuropsychiatric conditions [11][12][13][14][15][16][17]. Our systematic review and meta-analysis of tDCS in migraine found that repeated tDCS sessions may be a promising non-pharmacological treatment for reducing headache pain intensity and duration [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, repeated sessions can produce cumulative and long-lasting modulations of neural activity and neuroplasticity [9,10]. tDCS has therefore gained attention as a potential therapeutic tool for use in a range of various neuropsychiatric conditions [11][12][13][14][15][16][17]. Our systematic review and meta-analysis of tDCS in migraine found that repeated tDCS sessions may be a promising non-pharmacological treatment for reducing headache pain intensity and duration [18].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials have been conducted in patients with AD and mild cognitive impairment (MCI), and anodal tDCS was usually applied with a current of 2 mA for 20–30 min per session and target region at the DLPFC. Most of the trial findings (up to phase II) showed short-term cognitive improvement in delayed recall memory, executive function, language, and global cognition [ 6 ]. Furthermore, higher dosing or multiple-session protocols may induce greater effects in terms of behavioral change than single-session protocols.…”
Section: E Lectric and Magnetic Neuromodulationmentioning
confidence: 99%
“…Diverse pharmacological and physical therapies have been studied for MCI; unfortunately, to date, no consistent reports of long-term effectiveness have been published ( 5 ). However, increasing evidence suggests that transcranial direct current stimulation (tDCS) may be an effective add-on therapy to improve cognitive function in patients with MCI ( 2 , 6 , 7 ). tDCS is a non-invasive brain stimulation technique that involves placing electrodes on the scalp to apply a weak direct current to the brain cortex with the intent of modulating brain excitability ( 2 ).…”
Section: Introductionmentioning
confidence: 99%